2015
DOI: 10.1155/2015/293609
|View full text |Cite
|
Sign up to set email alerts
|

Response Surface Methodology for the Optimization of Preparation of Biocomposites Based on Poly(lactic acid) and Durian Peel Cellulose

Abstract: Response surface methodology was used to optimize preparation of biocomposites based on poly(lactic acid) and durian peel cellulose. The effects of cellulose loading, mixing temperature, and mixing time on tensile strength and impact strength were investigated. A central composite design was employed to determine the optimum preparation condition of the biocomposites to obtain the highest tensile strength and impact strength. A second-order polynomial model was developed for predicting the tensile strength and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 63 publications
1
13
1
Order By: Relevance
“…In the current study, we observed from SEM images that untreated wheat straw and kenaf fiber display lot of non-cellulosic components (lignin and pectin) scattered over the fiber (cellulosic part) surface, acting as cementing materials which bind several cellulosic microfibrils together. Similar observation was reported by Penjumras et al 39 The diameter of untreated wheat straw and kenaf fibers was in the order of several hundred micrometers. Unlike the synthetic fibers like carbon and glass, natural fibers are made of bundles containing fibrils that are in micron size, hence the word microfibrils.…”
Section: Resultssupporting
confidence: 90%
“…In the current study, we observed from SEM images that untreated wheat straw and kenaf fiber display lot of non-cellulosic components (lignin and pectin) scattered over the fiber (cellulosic part) surface, acting as cementing materials which bind several cellulosic microfibrils together. Similar observation was reported by Penjumras et al 39 The diameter of untreated wheat straw and kenaf fibers was in the order of several hundred micrometers. Unlike the synthetic fibers like carbon and glass, natural fibers are made of bundles containing fibrils that are in micron size, hence the word microfibrils.…”
Section: Resultssupporting
confidence: 90%
“…The response surface method analysis was carried out by running the experiment with highest efficiency, using an appropriate decision of design, plan, and to decide working conditions on an arrangement of controllable factors that offer ascent to an ideal reaction. The key to RSM are created utilizing straight polynomial models, for the most part first-degree and second degree models, with consistent reaction factors accepted, to be independent and normally distributed with consistent error variances [13][14]. Jiménez-Contreras et al summarized that, the RSM is an accumulation of scientific and mathematical methods that displaying and investigation of issues in which a reaction of intrigue is affected by a few factors and the target is to optimize the reaction [15].…”
Section: Response Surface Methodsmentioning
confidence: 99%
“…The sources with a p value less than 5% (< 0.05) were significant and stated as significant, whereas the sources with a p value bigger than 5% (>0.05) was stated as insignificant. A regression model was further broken into different orders of term in the model (linear, square and interaction) [14]. In linear terms, alkali concentration (p = 0.052) and immersion time (p=0.885) was bigger than 0.05 which indicated these factors were not significant.…”
Section: Regression Model For Tensile Strengthmentioning
confidence: 99%
“…Response surface method was previously employed to optimize preparation of biocomposites based on poly(lactic acid) and durian peel cellulose [21], preparation of carboxymethyl cellulose [22], and preparation of amaranth flour plasticized with glycerol and sorbitol [8]. Concentration of gelatin (A), glycerol (B) and citric acid (C) acted as independent variables, while the responses were tensile strength (T) and elongation at break (ε).…”
Section: Mechanical Analysismentioning
confidence: 99%